2011
DOI: 10.1017/s0954102011000435
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide emissions of Antarctic tourism

Abstract: Abstract:The increase of tourism to the Antarctic continent may entail not only local but also global environmental impacts. These latter impacts, which are mainly caused by transport, have been generally ignored. As a result, there is a lack of data on the global impacts of Antarctic tourism in terms of energy consumption and carbon dioxide emissions. This paper presents and applies a methodology for quantifying CO 2 emissions, both for the Antarctic vessel fleet as a whole and per passenger (both per trip an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 36 publications
(91 reference statements)
0
25
0
1
Order By: Relevance
“…However, when warming is combined with increased summer rain, the future Arctic regional carbon budget may depend on changes in summer rainfall, but not on temperature (Sharp et al ., ). Compared with the Qinghai‐Tibetan Plateau, biogeochemical cycles in the polar regions are probably less influenced by human activities and more impacted by ice and ocean processes, despite the already noticed effect of Antarctic tourism on carbon emissions (Farreny et al ., ).…”
Section: Comparisons With Polar Regionsmentioning
confidence: 99%
“…However, when warming is combined with increased summer rain, the future Arctic regional carbon budget may depend on changes in summer rainfall, but not on temperature (Sharp et al ., ). Compared with the Qinghai‐Tibetan Plateau, biogeochemical cycles in the polar regions are probably less influenced by human activities and more impacted by ice and ocean processes, despite the already noticed effect of Antarctic tourism on carbon emissions (Farreny et al ., ).…”
Section: Comparisons With Polar Regionsmentioning
confidence: 99%
“…The atmospheric distribution of PAHs over the Scotia, Bellingshausen and NW Weddell Seas showed that LRAT is a conveyor of PAHs to the Southern Ocean but its contribution seems to be smaller than the input from both, land based and ship-borne research and touristic activity 26 . Most ship traffic to the Antarctic takes place in the AP region and it has grown exponentially during the last 30 years 14 , 27 , 28 . On the other hand, this comparatively small region hosts approximately 43% of the Antarctic research facilities ( http://www.comnap.aq ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the bottom-top method is suitable for measuring small regions, such as the tourism footprint of local or scenic spots, without statistical or satellite tourism data. Visitor surveys can be customized to reflect greater levels of detail [28], as in studies on the Penghu Islands, China [32]; the city of Whistler, Canada [64]; and Antarctica [65]. Some exceptions in the literature include a study that measured tourism carbon emissions for Huangshan National Park, China [33], using the top-bottom method because it is a developed park with a complete database.…”
Section: Methodsmentioning
confidence: 99%